How international is the International Prostate Symptom Score? A literature review of validated translations of the IPSS, the most widely used self‐administered patient questionnaire for male lower urinary tract symptoms. Issue 2 (3rd November 2021) - Yao, Mark W.; Green, James S. A.
Abstract: Objectives: The International Prostate Symptom Score (IPSS) approaches its 30th anniversary. This ubiquitous clinical assessment tool is a standard in the assessment and research of lower urinary tract symptoms in men. The authors explore its history, development, and subsequent dissemination through validated translations across the world. An estimated global coverage is calculated and mapped according to language population. Methods: Embase and Medline literature searches were performed, with further hand searches of grey literature and online resources. Twenty‐two abstracts and journal articles validating language translations of the IPSS were reviewed in full and tabulated. Language population data were gathered from an official database and mapped. Results: The IPSS is available in 53 languages. Twenty‐seven languages have statistically or clinically validated translations for use in male patients. This corresponds to a conservative estimate of global population coverage of approximately 2.3 billion men, or 60% of the worldwide male population. Translation methodology involves forward and back translation. Statistical validation is performed with control patients. Cronbach's alpha is used for internal consistency, and Spearman's coefficient (p) or Pearson's coefficient (r) for test–retest reliability. Issues such as the emergence of altered versions deviating from original validated translations and translation difficulties due to cultural differences are observed. Further translational work is needed to validate versions of the IPSS in languages of the developing world. Conclusions: The IPSS is the most prevalent patient‐administered questionnaire used in urology across the world. There is no other clinical tool seen to have similar coverage. This paper aims to provide a roadmap for future clinical tools to acquire a similar level of translation and dissemination.